CompreTAP: feasibility and reliability of a new language comprehension mapping task via preoperative navigated transcranial magnetic stimulation - Kram, Leonie; Ohlerth, Ann-Katrin; Ille, Sebastian; Meyer, Bernhard; Krieg, Sandro (Cortex, 2024)
Objective - Stimulation-based language mapping approaches that are used pre- and intraoperatively employ predominantly overt language tasks requiring sufficient language production abilities. Yet, these production-based setups are often not feasible in brain tumor patients with severe expressive aphasia. This pilot study evaluated the feasibility and reliability of a newly developed language comprehension task with preoperative navigated transcranial magnetic stimulation (nTMS). - Methods - Fifteen healthy subjects and six brain tumor patients with severe expressive aphasia unable to perform classic overt naming tasks underwent preoperative nTMS language mapping based on an auditory single-word Comprehension TAsk for Perioperative mapping (CompreTAP). Comprehension was probed by button-press responses to auditory stimuli, hence not requiring overt language responses. Positive comprehension areas were identified when stimulation elicited an incorrect or delayed button press. Error categories, case-wise cortical error rate distribution and inter-rater reliability between two experienced specialists were examined. - Results - Overall, the new setup showed to be feasible. Comprehension-disruptions induced by nTMS manifested in no responses, delayed or hesitant responses, searching behavior or selection of wrong target items across all patients and controls and could be performed even in patients with severe expressive aphasia. The analysis agreement between both specialists was substantial for classifying comprehension-positive and -negative sites. Extensive left-hemispheric individual cortical comprehension sites were identified for all patients. Apart from one case presenting with transient worsening of aphasic symptoms, pre-existing language deficits did not aggravate if results were used for subsequent surgical planning. - Conclusion - Employing this new comprehension-based nTMS setup allowed to identify language relevant cortical sites in all healthy subjects and severely aphasic patients who were thus far precluded from classic production-based mapping. This pilot study, moreover, provides first indications that the CompreTAP mapping results may support the preservation of residual language function if used for subsequent surgical planning.
Online verfügbar: 22. November 2023, Artikelversion: 12. Dezember 2023
Gesehen am 22.03.2024